2015
DOI: 10.1590/1807-1929/agriambi.v19n3p224-230
|View full text |Cite
|
Sign up to set email alerts
|

Armazenamento do crambe em diferentes embalagens e ambientes: Parte I - Qualidade fisiológica

Abstract: R E S U M OObjetivou-se, neste trabalho, avaliar a qualidade fisiológica das sementes de crambe em diferentes condições de armazenamento, durante nove meses. O crambe com teor de água de 4,63% base úmida foi acondicionado nas embalagens laminada, polietileno tereftalato (PET) e polietileno de alta densidade (PEAD), as quais foram armazenadas nos ambientes: refrigerado, a 10 ± 1,19 °C e 34,84 ± 4,09% UR e natural, a 24,81 ± 1,82 °C e 54,93 ± 12,77% UR. O delineamento utilizado foi o inteiramente casualizado em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 13 publications
3
13
2
10
Order By: Relevance
“…Seeds under these conditions require higher nutrient intakes from their reserves to restore deteriorated membranes and reactivate their metabolism, compromising their vigour (Vanzolini & Nakagawa, 2005). The electrical conductivity values in this work are lower than those presented by other authors (Costa et al, 2012;Oliva, Biaggioni, & Cavariani, 2012;Bessa et al, 2015), but similar to those observed by Bezerra, Biaggioni, Silva, Sperotto, and Brandão (2015). Cruz et al (2013) evaluated five lots of crambe seeds and observed a variation from 58 to 877 mS cm -1 g -1 at different soaking times.…”
Section: Resultssupporting
confidence: 64%
“…Seeds under these conditions require higher nutrient intakes from their reserves to restore deteriorated membranes and reactivate their metabolism, compromising their vigour (Vanzolini & Nakagawa, 2005). The electrical conductivity values in this work are lower than those presented by other authors (Costa et al, 2012;Oliva, Biaggioni, & Cavariani, 2012;Bessa et al, 2015), but similar to those observed by Bezerra, Biaggioni, Silva, Sperotto, and Brandão (2015). Cruz et al (2013) evaluated five lots of crambe seeds and observed a variation from 58 to 877 mS cm -1 g -1 at different soaking times.…”
Section: Resultssupporting
confidence: 64%
“…However, this may be a result of the hygroscopic characteristics of the beans and relative humidity variation during the storage. Consequently, phenomena such as sorption and desorption likely occured, as described by Tiecker Junior et al (2014) and Bessa et al (2015) (Table 1). Moreover, throughout the 180 day storage period, the increase in the storage temperature decreased the equilibrium water content of the beans; this occurred because relative humidity decreased as the storage temperature increased and resulted in a lower equilibrium water content (Table 1).…”
Section: Resultsmentioning
confidence: 83%
“…With respect to relative humidity, the average value observed was 57.9 %, with a recorded maximum of 83.4 % and minimum of 47.3 %. Table 1 shows the oscillations in the water content of grains during storage, due to its hygroscopicity, and because of the non-controlled temperature and relative humidity that induce the sorption and desorption phenomena (Tiecker Junior et al 2014, Bessa et al 2015. During the 180 days of storage, it was also found that all the treatments exhibited increases in moisture content at 45 and 180 days, possibly because these two assessment points followed periods of higher relative humidity, thereby favoring sorption processes.…”
Section: Resultsmentioning
confidence: 99%